2021
DOI: 10.1038/s42003-021-01862-3
|View full text |Cite
|
Sign up to set email alerts
|

Lin28, a major translation reprogramming factor, gains access to YB-1-packaged mRNA through its cold-shock domain

Abstract: The RNA-binding protein Lin28 (Lin28a) is an important pluripotency factor that reprograms translation and promotes cancer progression. Although Lin28 blocks let-7 microRNA maturation, Lin28 also binds to a large set of cytoplasmic mRNAs directly. However, how Lin28 regulates the processing of many mRNAs to reprogram global translation remains unknown. We show here, using a structural and cellular approach, a mixing of Lin28 with YB-1 (YBX1) in the presence of mRNA owing to their cold-shock domain, a conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…On the other hand, YB-1 preserves RNA secondary structure, compacts mRNAs to maintain their dormancy, and positively regulates the formation of mRNA-rich condensates in some tissues. Precise spatio-temporal regulation of YB-1 mRNP activation can possibly be orchestrated by posttranslational events in the CTD and CSD ( 27 , 34 , 67 ) and protein partners ( 36 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, YB-1 preserves RNA secondary structure, compacts mRNAs to maintain their dormancy, and positively regulates the formation of mRNA-rich condensates in some tissues. Precise spatio-temporal regulation of YB-1 mRNP activation can possibly be orchestrated by posttranslational events in the CTD and CSD ( 27 , 34 , 67 ) and protein partners ( 36 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…In proliferating cells, YB-1 is generally abundant ( 32 , 33 ) which may contradict the notion that it is a global inhibitor of mRNA translation. Cellular signaling, YB-1 post-translational modification ( 34 , 35 ), and/or protein partners such as Lin28 ( 36 ) may either facilitate translation in proliferating cells or maintain YB-1-packaged mRNA in a dormant state, as evidence in testis ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study on colorectal cancer, LIN28A was found to promote the development and progression of disease by regulating the expression of the mRNA GEFT ( 38 ). Moreover, LIN28A has been confirmed to have the capacity to stabilize and modulate the expression of various mRNAs, including YB-packaged mRNA, RAN, and HSBP1 mRNA in tumors ( 40 42 ). More interestingly, it has been shown that LIN28A participated in regulating the differentiation and cell cycle progression of AML cells ( 43 ).…”
Section: Introductionmentioning
confidence: 98%
“…Highly expressed LIN28A can serve as a potential oncogenic factor that contributes to the tumorigenesis, development, and migration of ovarian, breast, liver, and colon cancers (27)(28)(29)(30)(31)(32)(33). Mechanism-wise, LIN28A can modulate the translation of its targeted mRNA and restrain let-7 expression in the posttranscriptional level, which both depend on the LIN28A protein's RNA-binding motif (34)(35)(36)(37)(38)(39)(40)(41)(42). For example, in a study on colorectal cancer, LIN28A was found to promote the development and progression of disease by regulating the expression of the mRNA GEFT (38).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of 4mer simulation, this loop-RNA contact served as an anchor and additional contacts were formed after certain RNA conformational changes. In a recent study, NMR and mutation studies indicated that K88, K89 (K98, K99 in LIN28A) play a role in electrostatic interactions with nucleic acids (83), and a recent study found a highly conserved Lys residue in YB1 protein (equivalent to K92 in Lin28B) is involved in ssDNA binding (84), as did the structural study of LIN28 on ssRNA nucleotides (72). Altogether, these evidences suggest that our graph-based approach is very effective in finding structure elements in RBP binding sites that are important in RBP-RNA recognition.…”
Section: Case Study: Lin28b-rna Docking and MD Simulationmentioning
confidence: 99%